STRATEGI PENGEMBANGAN MODAL SOSIAL UNTUK PENINGKATAN KEBERDAYAAN PETANI KARET DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Eka Rila Agustina; Ahmad Rifai; Kausar Kausar (Indonesian Journal of Agricultural Economics, 2020)
Social capital is something refers to the essence of social organization, as trust, norms and social network. Research objectives is to identify social capital owned rubber farmers at XIII Koto Kampar district, analyze the condition of a level independency of rubber farmers, analyze relations social capital to independency of rubber farmers and formulated the strategy of social capital development to increase the enpowerment of farmer. Method of the sample used the purposive sampling. The condition of social capital rubber farmers which were conducted at XIII Koto Kampar district considered to be high. Analysis factor of social capital, there are 5 main indicators formed from the previous 20 indicators. The condition of enpowerment at XIII Koto Kampar district is quite powerless in the category. The relation of social capital with independency of rubber farmers in a clockwise direction weak had at least a high. Strategy of social capital development to increase the enpowerment of farmer is to enhance distribution of the means of production to of the farming business of rubber in a gregarious manner, improve the quality of rubber farmers in a gregarious manner through to be an instructor, developing their activities in financing of the farming business of rubber in a gregarious manner paramedics are distributed to every over its role in taking function of the land, improve the quality of the production of rubber in a gregarious manner by means if information so that it can be suddenly find themselves in competition with rubber of foreign affairs